Dni ochrony przeciwpożarowej. (Malbork : [s.n.], 1958)
Afisz z programem obchodów 8-15.06.1958 r.
Keywords: Straż pożarna -- Polska -- Malbork -- 1945-1970 -- druki ulotne; Malbork (Polska) -- 1945-1970 -- druki ulotne